The Role Of Karang Taruna In Da’wah Community Economic Empowerment - Putra, Robby Aditya; Siwanto, Agus; Kurniawan, Andri; Masri, Muhammed Sahrin Haji (Institut Agama Islam Negeri (IAIN) Curup, 2023)
This research aims to determine the role of youth organizations in daâ€™wah economic empowerment through Village-Owned Enterprises (BUMK) in Goras Jaya Village, Bekri District, Central Lampung Regency. This research uses a qualitative approach, descriptive qualitative research, namely providing a complete picture of data obtained from observation, interviews and documentation. To determine the sample, use the Purposive Sampling technique. As for the criteria that the author provides, the sample is 8 people. The results of this research analysis show that the role of youth organizations in empowering the community's economy through red lemongrass cultivation groups is outlined in two stages which include the socialization stage and the empowerment process which consists of group formation, disbursement of funds. and capacity building as well as monitoring and evaluationÂ